Modulation of pro-inflammatory activation of monocytes and dendritic cells by aza-bis-phosphonate dendrimer as an experimental therapeutic agent - Degboé, Yannick (BioMed Central, 2014)
INTRODUCTION: Our objective was to assess the capacity of dendrimer aza-bis-phosphonate (ABP) to modulate phenotype of monocytes (Mo) and monocytes derived dendritic cells (MoDC) activated in response to toll-like receptor 4 (TLR4) and interferon γ (IFN- γ) stimulation. METHODS: Mo (n = 12) and MoDC (n = 11) from peripheral blood of healthy donors were prepared. Cells were preincubated or not for 1 hour with dendrimer ABP, then incubated with lipopolysaccharide (LPS; as a TLR4 ligand) and (IFN-γ) for 38 hours. Secretion of tumor necrosis factor α (TNFα), interleukin (IL) -1, IL-6, IL-12, IL-10 and IL-23 in the culture medium was measured by enzyme-linked immunosorbent assay (ELISA) and Cytokine Bead Array. Differentiation and subsequent maturation of MoDC from nine donors in the presence of LPS were analyzed by flow cytometry using CD80, CD86, CD83 and CD1a surface expression as markers. RESULTS: Mo and MoDC were orientated to a pro-inflammatory state. In activated Mo, TNFα, IL-1β and IL-23 levels were significantly lower after prior incubation with dendrimer ABP. In activated MoDC, dendrimer ABP promoted IL-10 secretion while decreasing dramatically the level of IL-12. TNFα and IL-6 secretion were significantly lower in the presence of dendrimer ABP. LPS driven maturation of MoDC was impaired by dendrimer ABP treatment, as attested by the significantly lower expression of CD80 and CD86. CONCLUSION: Our data indicate that dendrimer ABP possesses immunomodulatory properties on human Mo and MoDC, in TLR4 + IFN-γ stimulation model, by inducing M2 alternative activation of Mo and promoting tolerogenic MoDC.